AEIOU 프레임워크를 활용한 외국인의 키오스크 사용자 경험 분석 - 부산 관광지 무인발권기 중심으로 - 진위안위안; Yuan-yuan Jin; 이지혜; Ji-hye Lee (한국디자인포럼, 2025)
연구배경 관광지의 무인발권기 키오스크는 관광객의 편의를 위한 비대면 서비스 수단으로 활용되지만, 외국인관광객은 언어·문화적 장벽으로 사용에 어려움을 겪는다. 본 연구는 국내 관광지를 방문한 외국인 사용자를 대상으로 키오스크 사용 경험을 파악하고 사용자 중심의 디자인 개선 방향을 제시하는 데 목적을 둔다. 연구방법 본 연구는 부산의 관광지 중 한 곳인 해운대를 대상으로 외국인 사용자 경험을 파악하고자 2025년 5월 13일부터 5월 14일까지 2일간 해운대 블루라인파크에 위치한 키오스크를 사용하는 외국인 12명을 대상으로 참여 관찰을 진행하였고, 46명을 대상으로 심층 인터뷰를 통해 정성적 데이터를 수집하였다. 연구결과 현장 관찰 및 인터뷰 결과, 사용 과정의 페인포인트로 언어 설정의 시인성 부족, 정보 탐색 흐름의 불명확성, 결제 단계 번역 누락, 오류 시 피드백 부족의 인터페이스 요소가 주요 문제로 나타났다. 또한, 물리적 접근성과 시각적 안내의 부족과 같은 환경적 요소도 사용 혼란에 영향을 주었다. 결론 무인발권기 키오스크는 외국인 관광객에게 직관적이고 포용적인 경험을 제공하기 위해 언어 접근성, 정보구조, 피드백 시스템, 물리적 안내 요소 전반에서 개선이 필요하다. 본 연구는 실제 사용자 행태를 기반으로 UX 향상에 기여할 수 있는 실질적 디자인 방향을 제시했다는 점에서 의의가 있다. Background Unmanned ticketing kiosks at tourist destinations are widely used as a contactless service to enhance convenience for visitors. However, foreign tourists often face difficulties due to language and cultural barriers. This study aims to understand the kiosk usage experience of foreign users visiting tourist sites in Korea and to propose user-centered design improvements. Methods This study was conducted at Haeundae, a popular tourist destination in Busan. From May 13 to 14, 2025, participatory observation was conducted with 12 foreign users of the ticketing kiosk located in Haeundae Blueline Park. Additionally, in-depth interviews were conducted with 46 foreign visitors to collect qualitative data. Result Findings from field observations and interviews identified several key pain points in the user experience: low visibility of language selection, unclear information flow, missing translations during the payment process, and insufficient feedback when errors occurred. Environmental factors such as limited physical accessibility and a lack of clear visual guidance also contributed to user confusion. Conclusion To offer an intuitive and inclusive experience to foreign tourists, ticketing kiosks must improve in areas such as language accessibility, information structure, feedback mechanisms, and physical guidance elements. This study contributes to user experience (UX) enhancement by presenting actionable design directions based on real user behavior.